Odpowiedź:
[tex]a)\\\\\frac{5x-3}{4}+3=2x\ \ |\cdot4\\\\5x-3+12=8x\\\\5x+9=8x\\\\5x-8x=-9\\\\-3x=-9\ \ |:(-3)\\\\x=3\\\\\\b)\\\\x-\frac{2x+3}{5}=3\ \ |\cdot5\\\\5x-(2x+3)=15\\\\5x-2x-3=15\\\\3x-3=15\\\\3x=15+3\\\\3x=18\ \ |:3\\\\x=6[/tex]
[tex]c)\\\\4-\frac{x}{4}=2x-\frac{1}{2}\ \ |\cdot4\\\\16-x=8x-2\\\\-x-8x=-2-16\\\\-9x=-18\ \ |:(-9)\\\\x=2\\\\\\d)\\\\\frac{2x}{3}+4=\frac{x+2}{3}\ \ |\cdot3\\\\2x+12=x+2\\\\2x-x=2-12\\\\x=-10\\\\\\e)\\\\\frac{3x-2}{5}-2=\frac{x}{5}\ \ |\cdot5\\\\3x-2-10=x\\\\3x-12=x\\\\3x-x=12\\\\2x=12\ \ |:2\\\\x=6[/tex]